2007
DOI: 10.1002/art.23101
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcome following total hip arthroplasty: A controlled longitudinal study

Abstract: Objective. To assess long-term outcome and predictors of prognosis following total hip arthroplasty (THA) for osteoarthritis (OA). Methods. We studied 282 patients from 2 English health districts ϳ8 years after THA, along with 295 controls selected from the general population. Baseline data were collected by interview and examination, on sex, age, comorbidity, body mass index (BMI), and Short Form 36 (SF-36) functional status, and preoperative radiographic severity of OA was graded. Functional status was reass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
68
2
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 21 publications
11
68
2
1
Order By: Relevance
“…In line with other studies, the results of these studies also show that at followup, patients still had worse WOMAC pain and function scores and SF-36 physical function scores (3,28) than the reference group (age-and sexmatched controls), suggesting that patients receiving THR do not return to the same levels of pain and function as those of the general population.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In line with other studies, the results of these studies also show that at followup, patients still had worse WOMAC pain and function scores and SF-36 physical function scores (3,28) than the reference group (age-and sexmatched controls), suggesting that patients receiving THR do not return to the same levels of pain and function as those of the general population.…”
Section: Discussionsupporting
confidence: 89%
“…It has been shown to be highly cost effective and very good at relieving pain and disability as well as improving quality of life (1)(2)(3)(4). It is also among the most frequently used elective surgical procedures (ϳ170,000/year in Germany [5], ϳ70,000/year in England [6], and ϳ500,000/year in the US [7]).…”
Section: Introductionmentioning
confidence: 99%
“…Searches identified five studies reporting analyses of specific comorbid conditions identified before surgery and long-term patient-reported outcomes. 127,130,166,184,185 Two of these studies reported separate analyses of different comorbidities in the same cohort. 184,185 Study characteristics are summarised in Appendix 7 with brief details in Table 7.…”
Section: Total Hip Replacementmentioning
confidence: 99%
“…In another analysis of this cohort, the MD in change in SF-36 physical function was 25.8 points (95% CI 6.8 to 44.9 points) favouring patients with no diabetes. 184 However, both analyses were based on only eight patients with diabetes.…”
Section: Diabetesmentioning
confidence: 99%
“…From a group of patients with endometriosis, a significant negative correlation between VAS rating and quality of life has been evaluated by using MOS SF-36 questionnaire [57]. In addition, the same group has found a relation between hyperalgesia to pressure pain threshold measured and the impairment of SF-36 physical function as well as mental health parameters.…”
Section: Determining Quality Of Life Improvement After Surgery For Diementioning
confidence: 99%